2008
DOI: 10.1007/s10329-008-0092-3
|View full text |Cite
|
Sign up to set email alerts
|

Large rivers do not always act as species barriers for Lepilemur sp.

Abstract: Sportive lemurs constitute a highly diverse endemic lemur family (24 species) for which many biogeographic boundaries are not yet clarified. Based on recent phylogeographic models, this study aims to determine the importance of two large rivers (the Antainambalana and Rantanabe) in northeastern Madagascar as species barriers for Lepilemur seali. The Antainambalana River was previously assumed to act as the southern border of its distribution. A total of 1,038 bp of the mtDNA of four individuals stemming from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Although we cannot be sure whether the two new species occur north of this river, M. mittermeieri is now confirmed to occur south of it. Similar findings were recently described for the genus Lepilemur [Craul et al, 2008]. L. seali has also been confirmed to occur on both sides of the river.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Although we cannot be sure whether the two new species occur north of this river, M. mittermeieri is now confirmed to occur south of it. Similar findings were recently described for the genus Lepilemur [Craul et al, 2008]. L. seali has also been confirmed to occur on both sides of the river.…”
Section: Discussionsupporting
confidence: 88%
“…L. seali has also been confirmed to occur on both sides of the river. The presence of L. seali on both sides was suggested to be the result of a broad altitudinal range of this species, enabling animals to circumnavigate the headwaters of this large river and to maintain gene flow at least until recent times [Craul et al, 2008; see also Goodman & Ganzhorn, 2004]. The same could in principle apply to Microcebus sp.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Studies of great apes found that in chimpanzees ( Pan troglodytes ) [Gonder et al, ] and Bornean orangutans ( Pongo pygmaeus ) [Arora et al, ; Jalil et al, ], rivers apparently act as barriers to individual movement and thereby increase genetic differentiation between subpopulations on either side of the river. No barrier effect of rivers was detected in other smaller‐bodied, more arboreal primates like spider monkeys ( Ateles ) [Collins & Dubach, ], long‐tailed macaques ( Macaca fascicularis ) [Ruiter & Geffen, ] and a number of lemur species (Lemuriformes) [Craul et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of river barriers in primate speciation events is controversial. Lemurs in particular have been studied for the effect of rivers on gene flow and speciation, and some studies have claimed that rivers have a large effect [Wilme et al, 2006] while others have found little to no effect [Craul et al, 2008]. More concrete evidence for rivers as cultural barriers does exist, however.…”
Section: Rangementioning
confidence: 99%